Digital Revolution and Public Administration Innovation: Increasing the Efficiency and Responsiveness of Public Services - Chairussani Abbas Sopamena (Universitas Sultan Ageng Tirtayasa, 2024)
In the ever-growing digital era, public administration is faced with the challenge of increasing the efficiency and responsiveness of public services. The digital revolution has introduced various innovations in the management of public administration, providing opportunities for significant transformation in the way public services are provided and accessed by the public. This research aims to investigate how the digital revolution has influenced innovation in public administration and its impact on the efficiency and responsiveness of public services. This research uses a qualitative approach with descriptive methods. The research results show that the digital revolution and public administration innovation aims to increase the effectiveness and responsiveness of public services by utilizing information technology. Through the implementation of e-government systems, mobile applications and online platforms, the government can speed up administrative processes, facilitate public access, and strengthen interactions between government, business and society. This not only improves operational efficiency and the quality of public services, but also strengthens transparency, accountability and community participation in the development process. Technology enables the automation of routine tasks, increases the accessibility of services, accelerates the government's response to community needs, and opens the door to continuous innovation in the provision of public services. Thus, the digital revolution in public administration provides a strong foundation for improving relations between government and society and increasing effectiveness and efficiency in the provision of public services.